2005
DOI: 10.1097/01.don.0000152301.72828.61
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of a Polycaprolactone-Based Root Canal Filling Material to Degradation. I. Alkaline Hydrolysis

Abstract: Polycaprolactone, a thermoplastic aliphatic polyester, is reportedly susceptible to both alkaline and enzymatic hydrolyzes. This screening study examined the susceptibility of Resilon, a polycaprolactone-based root filling composite, to alkaline hydrolysis. There were 15-mm diameter disks of Resilon and Obtura gutta-percha prepared by compressive molding and immersed in 20% sodium ethoxide for 20 or 60 min. Control disks were immersed in ethanol for 60 min. These disks were examined using field-emission scanni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
87
1
5

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(96 citation statements)
references
References 32 publications
3
87
1
5
Order By: Relevance
“…12 In addition, the thermoplasticity of Resilon is higher than that of conventional and thermoplastic gutta-percha. 19 The thermoplastic properties of Resilon are attributed to the addition of polycaprolactone, which has a melting point of 60°C, 28 making it indicated for thermoplastic obturation techniques. 5,15,19 Gutta-percha cones are composed of barium sulfate, zinc oxide, wax, resin and gutta-percha, but the proportions of these components are not constant.…”
Section: Discussionmentioning
confidence: 99%
“…12 In addition, the thermoplasticity of Resilon is higher than that of conventional and thermoplastic gutta-percha. 19 The thermoplastic properties of Resilon are attributed to the addition of polycaprolactone, which has a melting point of 60°C, 28 making it indicated for thermoplastic obturation techniques. 5,15,19 Gutta-percha cones are composed of barium sulfate, zinc oxide, wax, resin and gutta-percha, but the proportions of these components are not constant.…”
Section: Discussionmentioning
confidence: 99%
“…97 All these in vitro leakage studies are evaluated over a number of days or weeks and it has been suggested that this may give a false perspective of the behaviour of resin sealers as they may degrade 88 or hydrolysis with time. 35,98 Therefore, before any meaningful conclusions can be made long-term evaluations and clinical studies are necessary.…”
Section: Sealing Ability/leakagementioning
confidence: 99%
“…104 It was suggested that a reason for Resilon's potential cytotoxicity may be due to the biodegradability of Resilon by enzymes and alkaline hydrolysis, which would expose the more toxic polymer matrix. 36,98 Epiphany sealer has been shown to be cytotoxic when compared to zinc oxide eugenol and epoxy-resin based sealers 100,105-110 with one study suggesting that it became more cytotoxic with increased exposure time. 111 However, it has also been demonstrated that although Epiphany was cytotoxic it did not effect the viability of human leucocytes.…”
Section: Biocompatibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…6 One study examined susceptibility of Resilon and gutta-percha to microbial biodegradation and showed minimal changes in the surface integrity of gutta-percha; however, Resilon exhibited severe surface pitting and erosion. 7 …”
Section: Introductionmentioning
confidence: 99%